Recent Advances and Strategies toward Polysulfides Shuttle Inhibition for High‐Performance Li–S Batteries - Huang, Youzhang; Lin, Liang; Zhang, Chengkun; Liu, Lie; Li, Yikai; Qiao, Zhensong; Lin, Jie; Wei, Qiulong; Wang, Laisen; Xie, Qingshui; Peng, Dong‐Liang (Advanced science, 2022)
Lithium–sulfur (Li–S) batteries are regarded as the most promising next‐generation energy storage systems due to their high energy density and cost‐effectiveness. However, their practical applications are seriously hindered by several inevitable drawbacks, especially the shuttle effects of soluble lithium polysulfides (LiPSs) which lead to rapid capacity decay and short cycling lifespan. This review specifically concentrates on the shuttle path of LiPSs and their interaction with the corresponding cell components along the moving way, systematically retrospect the recent advances and strategies toward polysulfides diffusion suppression. Overall, the strategies for the shuttle effect inhibition can be classified into four parts, including capturing the LiPSs in the sulfur cathode, reducing the dissolution in electrolytes, blocking the shuttle channels by functional separators, and preventing the chemical reaction between LiPSs and Li metal anode. Herein, the fundamental aspect of Li–S batteries is introduced first to give an in‐deep understanding of the generation and shuttle effect of LiPSs. Then, the corresponding strategies toward LiPSs shuttle inhibition along the diffusion path are discussed step by step. Finally, general conclusions and perspectives for future research on shuttle issues and practical application of Li–S batteries are proposed. This review summarizes the recent advances and strategies to suppress the shuttle effect of lithium polysulfides (LiPSs) in lithium–sulfur batteries. These strategies are composed of using the modified sulfur hosts to immobilize LiPSs, electrolyte systems to alleviate shuttle behavior, functional separator to intercept LiPSs, and anode surface engineering to avoid the chemical reaction between LiPSs and Li.